Sexual Attitudes among Students of Secondary Level 1-3 in Educational Opportunity Expansion Schools in Singburi Province, 2018 - Senla , Somkuan (Journal of Medical and Public Health Region 4, 2020)
Currently, knowledge, attitudes and skills related to sexual life among young people are low, making them vulnerable to exploitation and sexual abuse resulting in unwanted pregnancy and sexually transmitted infections, including HIV. The objective of this study was to assess attitudes about sex among students of secondary level 1-3 in educational opportunity expansion schools in Sing Buri Province. This questionnaire-based survey was conducted in 45 schools with a sample size of 1,863 students in 2017-2018. After the survey, students participated in Life Skills Program to prevent HIV. Data included students’ characteristics and sexual attitudes. Overall 25.4% of the students had high risk to have sex during their schooling period. Boys (30.4%) were more likely to have high risk than girls (19.4%). Of the survey students, 34.0% thought that having sex could be acceptable as a part of love; 15.2% thought that they could not refuse sex with their girlfriend/boyfriend; while 22.3% were not aware and could be exploited when they were in private or isolated spaces. Since students remain to have high risk of having sex during schooling and lack of skills to refuse sexual pressures with their boyfriends/girlfriends, it is essential to empower these students to make considered decisions on abstinence and relevant safe sex practices to prevent pregnancies and HIV infection.